PEMBEKALAN MENGENAI JURNAL PENYESUAIAN DI SMA NEGERI 2 JAKARTA TERKAIT DENGAN PROGRAM MBKM ASISTENSI MENGAJAR - Dania; Susanti, Merry (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
This teaching assistance report provides information regarding adjusting journal at SMA Negeri 2 Jakarta related to the MBKM program called “Asistensi Mengajar di Satuan Pendidikan”. Adjusting journal is a record of transactions carried out at the end of an accounting period to adjust the balances of certain accounts before preparing financial reports. It is hoped that with this provision, students at SMA Negeri 2 Jakarta can understand the importance of adjusting journals in the accounting process and apply them well in their learning. The lesson has provided positive results for students and uses a method where students can understand adjusting journals.